LABOR LAW AND ITS ACADEMIC TEACHING IN THE SCIENTIFIC PRODUCTION OF THE JOURNAL OF LEGAL SCIENCES - Fajardo Torres, Anahí (2026)
The academic teaching of Labor Law at the Facultad de Derecho has been complemented by the scientific publications of the Revista de Ciencias Jurídicas. Hence, on the occasion of the anniversary of this prestigious Journal, the opportunity is presented to reflect on that contribution and current reality based on legal reforms, as well as its validity and relevance as a source of knowledge, to achieve greater excellence in the teaching-learning processes of the student as a future professional in this area. The possibility of reviewing and updating some content of the articles is also presented based on what is contained in the Labor Procedural Reform that modernized labor legislation, as well as guaranteeing faster and more expeditious access to justice to resolve conflicts at legal jurisdiction.